Construction material management for Eastern Seaboard Project - Pornchai Prasart-intara; Pichai Nimityongskul; Ping Kunawatsatit; Pama, Ricardo P.; Chauhan, Gopal; Government of Denmark (Bangkok : Asian Institute of Technology, 1986)
This study examines and analyzes the optimal planning and scheduling of construction materials under non-stationary demand for the Eastern Seaboard Project in the eastern part of Thailand. Th ere is a known demand requirement to be met in each period from the quantity breakdown of project. Algorithms for finding the optimal policy are under the assumption that all costs are described by linear function . Substantially , the optimal material delivery schedule , associated levels of inventory, employment in the procurement a nd delivery processes, and provided storage space for the period under analysis are determined by using the application of integer linear programming model. For this study, the investigation of locally available satisfactory construction material sources for the project has to be taken in to consideration so that an economic hauling distance can be attained, Material cost of these sources has also to be considered.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Eastern Seaboard Project; Building materials -- Research